2020
DOI: 10.1108/aeat-12-2019-0253
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of emission values from commercial flights at Dalaman international airport Turkey

Abstract: Purpose This study aims to present atmospheric emissions (NOx, CO and HC) of commercial flights at Dalaman Airport for the years between 2016 and 2018. Design/methodology/approach Growing up, the potential for domestic and international airports will cause an increase in air transportation. Increasing demand for air transportation will cause adverse environmental impacts as well as positive economic contributions. Finding negative environmental effects and searching for solutions is an essential first step. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Noise and pollutant emissions are among the leading environmental problems in the landing and takeoff (LTO) cycles of aircraft around the airport. In addition, pollutant emissions have serious negative effects on local air quality (Kafali and Altuntas, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Noise and pollutant emissions are among the leading environmental problems in the landing and takeoff (LTO) cycles of aircraft around the airport. In addition, pollutant emissions have serious negative effects on local air quality (Kafali and Altuntas, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The author obtained the aircraft emissions as 247.33 t/y for NOx, 161.21 t/y for CO and 20.24 t/y for HC) at Tbilisi international airport (Tokuslu, 2020). Kafali and Altuntas (2020) (Kafali and Altuntas, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tokuslu (2020) assessed the aircraft emissions during LTO cycles for the year 2018 at Tbilisi International Airport in Georgia and calculated aircraft emissions as 428.78 t/y (247.33 t/y for NO x , 161.21 t/y for CO and 20.24 t/y for HC). Kafali and Altuntas (2020) present aircraft emissions of commercial flights at Dalaman Airport for the years between 2016 and 2018 under three different units. Ekici and S öhret (2020) evaluated the environmental and economic impact of emitted greenhouse gas emissions of aircraft operating at the Antalya International Airport and found that the aircraft family of B737 has the highest value with 630,633.3 GWP and 39,723.4 costs.…”
Section: Introductionmentioning
confidence: 99%